A Becoming, Humanist Child: An analysis of Learning and Care in the Swedish Curriculum for the Preschool (Lpfö 18) - Jacob Billmayer; Martha Pastorek Gripson; Disa Bergnehr (University of Aberdeen, School of Education, 2019)
A new, revised curriculum for the Swedish preschool came into effect in July 2019. According to the National Agency of Education, it differs from its predecessor by putting a greater emphasis on care and teaching. This paper studies how the child is conceptualized in relation to learning and care in the new curriculum. Informed by a posthumanist approach and childhood studies, it scrutinizes how the child is positioned as a being and/or becoming child, an entangled and/or separate child, and, an active and/or passive child. Furthermore, it explores how the child appears in relation to human and non-human agents. The dominant, recurring conceptualization of the child is the child as becoming and passive. Learning and caring processes mainly come across as unidirectional - from adult to child - and future orientated. Although the preschool child is connected to a social context, the child predominantly appears as separate from others rather than entangled.